The Effect of Principal’s Leadership Style and Teacher’s Job Satisfaction on Teacher’s Performance - Yuniarti, Yuniarti; Ahmad, Syarwani; Fitriani, Yessi (Journal of Social Work and Science Education, 2023)
The purpose of this study is to identify and assess the effects of the principal’s leadership style, teacher job satisfaction, and the combination of the two on the performance of elementary school teachers in the Sosoh Buay Rayap District. This study uses descriptive quantitative methods. There were 90 participants in this study, all of them were elementary school teachers employed by the Sosoh Buay Rayap sub-district. The entire research population is used as the research sample because the overall population is less than 100. Using surveys, observation, and interviews as data collecting methods. The findings demonstrated that the principal’s leadership style had an impact on teacher performance, as indicated by the t-count = 2.845, t-count > t-table 1.960. It is possible to conclude that the relationship with subordinates and their performance will improve as a result of greater leadership. 46.4% of teachers said that their job satisfaction at school affects their performance. The F-count score is 12.420 > F-table, indicating that the principal’s leadership style and work satisfaction have a considerable impact on teacher performance, according to the principal’s leadership style and contentment with teacher performance.